2008
DOI: 10.1186/1477-5956-6-28
|View full text |Cite
|
Sign up to set email alerts
|

SELDI-TOF-MS determination of hepcidin in clinical samples using stable isotope labelled hepcidin as an internal standard

Abstract: Background: Hepcidin is a 25-residue peptide hormone crucial to iron homeostasis. It is essential to measure the concentration of hepcidin in cells, tissues and body fluids to understand its mechanisms and roles in physiology and pathophysiology. With a mass of 2791 Da hepcidin is readily detectable by mass spectrometry and LC-ESI, MALDI and SELDI have been used to estimate systemic hepcidin concentrations by analysing serum or urine. However, peak heights in mass spectra may not always reflect concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 28 publications
3
52
0
2
Order By: Relevance
“…In addition, Ganz et al (29 ) developed a competitive (c)ELISA for human serum hepcidin. Other groups have also reported reliable hepcidin assays that can be divided in 3 main methodologies: (a) MS (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95); (b) immunochemical assays, comprising cRIA (96,97 ), cELISA (13,29,98,99 ), and a 2-site ELISA (100 ); and (c) a ligand-binding assay (43 ) ( Table 1). Of the currently available commercial immunochemical research kits for serum hepcidin, we found the RIA and enzyme-immunoassay kits of Bachem (purchased November 2009 and August 2010, respectively) to be suitable to differentiate between hepcidin concentrations in serum samples of controls and patients with various iron disorders, whereas the bioactive hepcidin kit of DRG Instruments, (purchased October 2009) gave similar concentrations for all samples and could not discriminate between iron metabolism disorders (unpublished results).…”
Section: Second-generation (Quantitative) Hepcidin Assaysmentioning
confidence: 99%
“…In addition, Ganz et al (29 ) developed a competitive (c)ELISA for human serum hepcidin. Other groups have also reported reliable hepcidin assays that can be divided in 3 main methodologies: (a) MS (85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95); (b) immunochemical assays, comprising cRIA (96,97 ), cELISA (13,29,98,99 ), and a 2-site ELISA (100 ); and (c) a ligand-binding assay (43 ) ( Table 1). Of the currently available commercial immunochemical research kits for serum hepcidin, we found the RIA and enzyme-immunoassay kits of Bachem (purchased November 2009 and August 2010, respectively) to be suitable to differentiate between hepcidin concentrations in serum samples of controls and patients with various iron disorders, whereas the bioactive hepcidin kit of DRG Instruments, (purchased October 2009) gave similar concentrations for all samples and could not discriminate between iron metabolism disorders (unpublished results).…”
Section: Second-generation (Quantitative) Hepcidin Assaysmentioning
confidence: 99%
“…Recently, Ward et al (34) used an isotopically labeled hepcidin as an internal standard for the quantitation of hepcidin using SELDI-TOF MS. No accuracy and recovery data have been presented; however, there is good intraday (Ͻ10%) and interday (Ͻ20%) precision with this assay. The lowest quantity of internal standard reliably detected in serum was 10 ng/ml, and this study found the average hepcidin concentration in healthy women to be 50 ng/ml.…”
Section: Surface Enhanced Laser Desorption/matrix-assisted Laser Desomentioning
confidence: 99%
“…Some methods use an internal standard, either hepcidin analogs or bioactive hepcidin-25 synthesized with stable isotopes. [3][4][5][6][7][8][9][10] Recently, immunochemical (IC) assays for hepcidin-25 have also been developed, which comprise of competitive radioimmunoassays (RIA) 11 and enzyme-linked immunosorbent assays (ELISA). 12,13 Currently there is no reference method for hepcidin measurements.…”
Section: Introductionmentioning
confidence: 99%